The Equity Portfolio Selection at Euronext - Meiyu LU (Communications of International Proceedings, 2021)
European financial markets have always been the dominant region of the world economy. It is therefore important for a given investor to understand how to better allocate assets and find the best portfolio strategy. A good portfolio can help investors to diversify the risk and reduce the impact of economic fluctuations. In this paper, we analyze the closing prices of stocks on the Euronext exchange in the decade before the outbreak of the pandemic. During this period, the European economy was recovering from the financial crisis of 2008. We will compare the performance of portfolio strategies under the Markowitz model and the Tobin model. At the same time, we will calculate and analyze indicators for measuring portfolio performance, i.e. Sharpe ratio Maximum drawdown and Jensen´s alpha. We optimize the portfolio under different functions and constraints. Ultimately, based on the results of the analysis, we will make some investment recommendations.
Keywords: Euronext; Markowitz model; Portfolio Optimization; Tobin model; Sharpe ratio.